Impact of Match Type on Exercise Volume and Intensity of Semi-Professional Basketball Referees During a Competitive Season. Issue 4 (2nd October 2021) - Leicht, Anthony S.; Connor, Jonathan; Conduit, Nathan; Vaquera, Alejandro; Gómez, Miguel A.
ABSTRACT: Identification of the exercise volume and intensity of basketball referees, across competitive match types based on competition sex and level, would assist in developing appropriate training regimes. Purpose : The aims of this study were to quantify and compare the exercise volume and intensity encountered by semiprofessional basketball referees during different match types across a competitive season. Method : Sixteen referees participated and were monitored for absolute and relative PlayerLoad (PL) using microsensors during 25 semiprofessional matches (12 men's, 13 women's, 17 regular season, eight playoff). Comparisons between match types (men's vs. women's; regular season vs. playoff) were examined via independent t-tests or Mann–Whitney U tests, and repeated measures ANOVA with the magnitude of differences calculated via effect size. Results : Referees experienced an absolute PL of 365 arbitrary units (AU) per match that was similar for men's, women's, regular season, and playoff matches during a competitive season. Relative PL was significantly greater (5.35 ± 0.82 vs. 4.26 ± 0.59 AU.min −1, p < .001, effect size = 1.57) during women's matches with a greater proportion of each quarter and match spent within PL band 2 compared to men's matches (11.6 ± 2.2 vs. 8.8 ± 1.4%, p < .001, effect size = 1.53), likely due to a reduced number of referees officiating. Minimal differences existed between the regular season and playoff matches for absolute PL, relative PL, and proportion of quarter/match time within PL bands. Conclusion : The current study confirmed that referees experienced considerable exercise volume and intensity per match during a competitive season with these influenced primarily by referee configuration. The current results provide crucial information to develop effective training regimes for referees during a competitive season.